A weighted extremal function and equilibrium measure - Bos, Len; Levenberg, Norman; Ma'u, Sione; Piazzon, Federico (MATHEMATICA SCANDINAVICA, 2017)
We find an explicit formula for the weighted extremal function of $\mathbb{R}^n\subset \mathbb{C}^n$ with weight $(1+x_1^2+… +x_n^2)^{-1/2}$ as well as its Monge-Ampère measure. As a corollary, we compute the Alexander capacity of $\mathbb{RP}^n$.